2005
DOI: 10.3748/wjg.v11.i32.5037
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in peripheral blood mononuclear cells of SARS patients

Abstract: Gene expression in SARS patients mirrors a host state of inflammation and anti-viral immunity at the transcription level, and understanding of gene expression profiles may make contribution to further studies of the SARS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…In agreement with the above consideration, it has been reported that several IFN-stimulated genes, such as PKR, GBP-1/2, CXL-10/11, and JAK/STAT signal pathway were down-regulated in SARS patients with acute severe phase compared to patients with the convalescent phase [11] .…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In agreement with the above consideration, it has been reported that several IFN-stimulated genes, such as PKR, GBP-1/2, CXL-10/11, and JAK/STAT signal pathway were down-regulated in SARS patients with acute severe phase compared to patients with the convalescent phase [11] .…”
supporting
confidence: 68%
“…Altogether, the data presented in this study, along with previous results [10][11][12][13][14][15][16][17][18][19] , demonstrate that SARS-CoV is a weak inducer of IFN-␣ , -␤ and -␥ . The potential limitations of our study include the fact that we did not compare IFN response in SARS-CoV-infected PBMCs with those in other relevant human virus.…”
mentioning
confidence: 61%
“…Most studies that use tissue or blood samples from SARS patients did not find a strong interferon response in these patients [1517,38,39]. This apparent absence of interferon induction in human SARS patients can be explained by the fact that good quality tissue and blood samples from SARS patients were not readily available and even more by the fact that samples were often taken at the time of death, for example, late during infection, making type-I interferon levels difficult to detect.…”
Section: Interferon Induction By Sars-covmentioning
confidence: 99%
“…Several studies have shown that peripheral-blood mononuclear cells (PBMCs) from SARS-CoV-infected individuals produce high amounts of inflammatory cytokines and chemokines, but not type I IFNs. [22][23][24] Furthermore, in vitro studies have shown that neither macrophages nor monocyte-derived DCs respond to SARS-CoV infection with significant IFN-␣ production. [25][26][27][28] Nonetheless, there is clear evidence that treatment with recombinant IFN-␤ or IFN-␣ can inhibit SARS-CoV replication in vitro, [29][30][31] and, most importantly, diminish the severity of SARS-CoV infection in vivo.…”
mentioning
confidence: 99%